Exploring Non-Muslim Engagement in Islamic Financial Institutions: Socio-Economic Dimensions of Islamic Finance in Multicultural Societies - Khoirul Anwar; Faridhatun Nasikah (JURNAL AT-TURAS, 2025)
This study aims to explore the participation of non-Muslims in Islamic financial institutions within the multicultural context of Singosari, Malang Regency. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and institutional document analysis. The findings reveal that non-Muslim participation is evident yet selective, with the highest interest directed toward universal products such as savings, microenterprise financing, and investment schemes emphasizing transparency and profit-sharing. Institutional factors, including regulation and human resource capacity, significantly influence the effectiveness of inclusion, as national policies have not been fully integrated at the local level. Market structure analysis indicates that hybrid business models incorporating fintech demonstrate greater outreach to non-Muslim communities compared to traditional models, although concerns over data security remain a critical barrier. Educational and communication strategies overly reliant on Islamic terminology were found to be less effective, whereas approaches emphasizing universal benefits, product visualization, and cross-faith testimonials proved more acceptable. Digital product innovations offering transparent contract explanations and profit-sharing simulations enhanced interest, yet digital literacy gaps persisted as obstacles. The stigma of exclusivity in Islamic finance continues to pose socio-psychological challenges, which can only be mitigated through multi-stakeholder involvement, including regulators, financial institutions, community leaders, and academics. This research underscores the importance of cross-religious financial inclusion strategies to strengthen social cohesion and support national financial inclusion agendas.